Analisis Kadar Kafein Biji Kopi Arabika Dengan Variasi Temperatur Sangrai Yang Tumbuh Di Aek Sabaon Tapanuli Selatan - Mey Linda Hasibuan; Sumardi Sumardi; Nilsya Febrika Zebua; Nurmala Sari (Journal of Pharmaceutical and Sciences, 2023)
Roasting can change the physical properties and chemical properties of coffee beans such as the composition of the chemical compounds contained in them, namely caffeine compounds. Caffeine is one of the compounds contained in coffee beans. It is necessary to analyze the differences in the roasting profile in the roasting process of coffee beans to find out if there is a difference in caffeine levels in coffee based on variations in roasting temperature. This study was conducted to determine the caffeine content in arabica coffee grown in Aek Sabaon Village, Marancar District, South Tapanuli Regency with variations in roasting temperatures. The roasting method is carried out in a modern way using a coffee roasting device equipped with a thermometer. The extraction method used is liquid-liquid extraction using chloroform as the solvent. The determination of arabica coffee caffeine levels with variations in roasting temperatures was carried out using the UV-vis spectrophotometry method using HCl 0.1 N as solvent. The results showed caffeine content in arabica coffee samples with variations in roasting temperatures with temperatures of 180°C, 200°C and 210°C respectively; 11.23%, 11.30% and 13.92%. Statistically, the test using ANOVA showed a difference in caffeine levels in the variation in roasting temperature which was not very significant because the significance of p > 0.05 and in the t Test it met the requirements of the significance value p < 0.05 so that it showed a free variable positive and significant effect on the bound variable.